Rainforests - Aldis, Rodney (New York Dillon Press, 1991)
Examines the plant and animal life of the rainforests and the threats to their continued existence.
Includes index.
Keywords: Rain forest ecology -- Juvenile literature; Rain forests -- Juvenile literature; Rain forest conservation -- Juvenile literature; Rain forests; Rain forest ecology; Ecology